Comparison of chemical profiles between the root and aerial parts from three Bupleurum species based on a UHPLC-QTOF-MS metabolomics approach - Lin Zhu; Zhi-Tao Liang; Tao Yi; Yue Ma; Zhong-Zhen Zhao; Bao-Lin Guo; Jian-Ye Zhang; Hu-Biao Chen (BMC, 2017)
Abstract Background Bupleuri Radix (Chaihu) represents one of the most successful and widely used herbal medicines in Asia for the treatment of many diseases such as inflammatory disorders and infectious diseases over the past 2000 years. In the Chinese Pharmacopoeia, Chaihu is recorded as the dried roots of Bupleurum chinense DC. and B. scorzonerifolium Willd. (Umbelliferae). However, the widespread demand for the herb has tended to far outstrip the supply. Whether the aerial parts, which account for 70 ~ 85% of the dry weights of Bupleurum species, could be used as an alternative for the root has become an important scientific issue for the sustainable utilization of Bupleurum species. On the other hand, in some areas including the southeast of China as well as in Spain, the aerial parts of Bupleurum species have already been used in the folk medications. Therefore, to clarify whether the root and aerial parts of Bupleurum species are "equivalent" in the types and quantities of chemical constituents which subsequently influence their biological activities and therapeutic effects is of great importance for both the rational and sustainable use of this herb. Methods In the present study, the chemical profiles between the root and aerial parts of Bupleurum species from different species and collected from various locations were analyzed and compared by the ultra-high performance liquid chromatography quadrupole/time of flight-mass spectrometry (UHPLC-QTOF-MS). Results A total of 56 peaks were identified in the root and/or aerial parts from different batches of Bupleurum species, by comparison of references standards or with those reported in the literature. Principal Component Analysis (PCA) was conducted for displaying the differentiating clustering between these two parts. Conclusion The results disclosed the distinct variations between them, which indicated that the aerial parts could not be used as an alternative of root from a chemodiversity perspective. The differentiating markers resulted from the PCA analysis could also be utilized for the differentiation between them. Further validation of their biological differences is anticipated in the future study.